The Schur Multiplicative and Harmonic Convexities for Three Classes of Symmetric Functions. (13th December 2018) - Sun, Ming-bao; Li, Xin-ping; Zhang, Ying-hui; Zhang, Zai-yuan
Abstract : We investigate the Schur harmonic convexity for two classes of symmetric functions and the Schur multiplicative convexity for a class of symmetric functions by using a new method and generalizing previous result. As applications, we establish some inequalities by use of the theory of majorization, in particular, and we give some new geometric inequalities in then -dimensional space.